Breast Cancer Surveillance Following Ovarian Cancer in BRCA Mutation Carriers. Issue 10 (26th October 2020) - Fong, Abigail; Cass, Ilana; John, Catherine; Gillen, Jessica; Moore, Kathleen M.; Gangi, Alexandra; Walsh, Christine; Li, Andrew J.; Rimel, Bobbie J.; Karlan, Beth Y.; Amersi, Farin
BRCA 1 or 2 mutations result in higher cancer risk for breast cancer (BC) and epithelial ovarian cancer (EOC) for carriers than exists in the general population. Optimal breast imaging surveillance in these patients has not been well defined. An Institutional Review Board-approved, multi-institutional retrospective chart review was performed. Patients diagnosed with BRCA-associated EOC between 1990-2015 were identified; demographic and clinical data were collected and analyzed. 192 BRCA mutation–positive patients with EOC were identified. 16/192 (8.3%) women were diagnosed with BC following EOC, at a median of 50 (range 5-327) months following EOC diagnosis and median age 59.5 (45-84) years. Breast cancer was most commonly detected on mammogram 7/16 (44%) or clinical exam 7/16 (44%). 2/16 (12.5%) had occult BC found during risk-reducing mastectomy. 14 (88%) had early-stage (0-2) disease. At mean follow-up of 8.1 years, 6 (37.5%) patients with BC following EOC had died due to EOC. The risk of BC diagnosis following EOC in BRCA mutation carriers is low; most of these BCs are early stage and diagnosed with mammography or physical exam. Overall, survival in BRCA mutation carriers is dominated by EOC-related mortality. Breast cancer surveillance in BRCA mutation carriers following EOC should prioritize nonsurgical strategies.